A cross‐sectional, case‐control study of intracranial arterial wall thickness and complete blood count measures in sickle cell disease. (16th December 2020) - Yuan, Shuai; Jordan, Lori C.; Davis, Larry T.; Cogswell, Petrice M.; Lee, Chelsea A.; Patel, Niral J.; Waddle, Spencer L.; Juttukonda, Meher; Sky Jones, R.; Griffin, Allison; Donahue, Manus J.
Summary: In sickle cell disease (SCD), cerebral oxygen delivery is dependent on the cerebral vasculature's ability to increase blood flow and volume through relaxation of the smooth muscle that lines intracranial arteries. We hypothesised that anaemia extent and/or circulating markers of inflammation lead to concentric macrovascular arterial wall thickening, visible on intracranial vessel wall magnetic resonance imaging (VW‐MRI). Adult and pediatric SCD ( n = 69; age = 19.9 ± 8.6 years) participants and age‐ and sex‐matched control participants ( n = 38; age = 22.2 ± 8.9 years) underwent 3‐Tesla VW‐MRI; two raters measured basilar and bilateral supraclinoid internal carotid artery (ICA) wall thickness independently. Mean wall thickness was compared with demographic, cerebrovascular and haematological variables. Mean vessel wall thickness was elevated ( P  < 0·001) in SCD (1·07 ± 0·19 mm) compared to controls (0·97 ± 0·07 mm) after controlling for age and sex. Vessel wall thickness was higher in participants on chronic transfusions ( P  = 0·013). No significant relationship between vessel wall thickness and flow velocity, haematocrit, white blood cell count or platelet count was observed; however, trends ( P  < 0·10) for wall thickness increasing with decreasing haematocrit and increasing white blood cell count were noted. Findings are discussed in the context of how anaemia and circulating inflammatory markers may impact arterial wall morphology.